Cooperação processual e dever de fundamentação: a repercussão da colaboração processual no dever de fundamentação das decisões judiciais. - Santos, Lucas Miguel Medeiros de Oliveira (2022)
What is the dogmatic repercussion of procedural cooperation on the duty to provide reasons for judicial decisions? This research has destined itself to investigate the influence of procedural cooperation (art. 6.º, CPC) on the reasoning of judicial pronouncements (art. 93, IX, CRFB/88). As a starting point, it was raised the following hypothesis: 1) The procedural cooperation affects the duty to state reason; 2) the procedural is an instrument of judicial decisions control; 3) the non-complying of the duty of cooperation on the reasoning on judicial decisions results in judicial consequences. This work has a dogmatic nature and uses hermeneutics as a normative interpretation technique to answer the proposed problem. In the construction of this work, it was sought to explore the critical literature that addresses the procedural cooperation, to organize the institute based on art. 6.º of CPC, and to investigate the normative interpretation of dispositive that affect the duty of stating reason based on the concepts that were built throughout the research. As a result, the first hypothesis was confirmed, the procedural cooperation reverberates on the duty to state reasons through one of its purposes. It confirmed the second hypothesis, the cooperation makes it possible the decision control by third parties. Lastly, confirmed partially the third hypothesis, the non-complying of cooperation duty on the reasoning makes it possible to legal consequence, but it is conditioned to legal recognition, its consequence is not automatic.